The reading process: An overview / Mohd. Noor Azman Othman - Othman, Mohd. Noor Azman (Universiti Teknologi MARA Cawangan Pahang, 2000)
Many of us regard reading as an activity that we do almost every minute in our lives as something that is very simple. To many, reading means to comprehend what has been printed on a piece of paper that has been written by a writer. Reading to a linguist is more than comprehending printed text. There are some complex activities that take place in the our brain when we read. What are the activities involved in the process of comprehending a text? Sometimes there are even models and strategies involved in the effort of trying to understand a text. This article discusses reading from the point of view a linguist so that the process of comprehending a text will become clear to us all.